2008
DOI: 10.1172/jci35781
|View full text |Cite
|
Sign up to set email alerts
|

Hsp104 antagonizes α-synuclein aggregation and reduces dopaminergic degeneration in a rat model of Parkinson disease

Abstract: Parkinson disease (PD) is characterized by dopaminergic neurodegeneration and intracellular inclusions of α-synuclein amyloid fibers, which are stable and difficult to dissolve. Whether inclusions are neuroprotective or pathological remains controversial, because prefibrillar oligomers may be more toxic than amyloid inclusions. Thus, whether therapies should target inclusions, preamyloid oligomers, or both is a critically important issue. In yeast, the protein-remodeling factor Hsp104 cooperates with Hsp70 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
263
1
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 184 publications
(266 citation statements)
references
References 69 publications
1
263
1
1
Order By: Relevance
“…23,24 Hsp104 disassembles preformed α-syn amyloid fibers as well as its preamyloid oligomeric precursors. 23,24 In addition, Hsp104 suppressed α-syninduced dopaminergic neurodegeneration in the rat substantia nigra.…”
Section: Applying Chaperones To Restore Proteostasismentioning
confidence: 99%
See 3 more Smart Citations
“…23,24 Hsp104 disassembles preformed α-syn amyloid fibers as well as its preamyloid oligomeric precursors. 23,24 In addition, Hsp104 suppressed α-syninduced dopaminergic neurodegeneration in the rat substantia nigra.…”
Section: Applying Chaperones To Restore Proteostasismentioning
confidence: 99%
“…23,24 Hsp104 disassembles preformed α-syn amyloid fibers as well as its preamyloid oligomeric precursors. 23,24 In addition, Hsp104 suppressed α-syninduced dopaminergic neurodegeneration in the rat substantia nigra. 24 Furthermore, we have demonstrated that Hsp104 disassembles preformed aggregates and amyloids comprised of Aβ, tau, polyglutamine, and amylin in vitro.…”
Section: Applying Chaperones To Restore Proteostasismentioning
confidence: 99%
See 2 more Smart Citations
“…For example, treating a polyglutamine disease model with an antiulcer drug, geranylgeranylacetone (GGA), which can induce the expression of different Hsps, could suppress the accumulation of pathogenic proteins and ameliorate the related phenotype (Katsuno et al 2005). In a rat model of Parkinson's disease, Hsp104 was found to be similarly efficient (Lo Bianco et al 2008). An increased level of expression of small Hsps and Hsp70 in the brain of AD patients has been reported in a number of studies (Perez et al 1991;Muchowski and Wacker 2005).…”
Section: Introductionmentioning
confidence: 99%